Beyond Justice Perceptions: The Role of Interpersonal Justice Trajectories and Social Class in Perceived Legitimacy of Authority Figures - Liang, Juan; Chen, Xiaoyun; Li, Tian; Wang, Yaxin (Frontiers in Psychology, 2021)
There is considerable evidence that the experience of justice is associated with perceived legitimacy of authority, but there has been no research about this association when considering past rather than current fairness. Based on the fairness heuristic theory, we tested the hypothesis that interpersonal justice trajectories positively affect perceived legitimacy of the authority; we also tested whether social class moderated this effect. Community residents (N = 111; 54 women) rated the authority's fairness on 16 consecutive weeks and rated perceived legitimacy on the 16th week. The results of latent growth modeling showed that the trajectory of interpersonal justice scores leading up to the final week significantly predicted perceived legitimacy, regardless of the current experience of interpersonal fairness. Tests of moderation showed that the legitimacy perceptions of individuals of lower subjective social class were significantly affected by interpersonal justice trajectories, whereas this was not the case among individuals of higher subjective social class. The results are discussed in terms of their implications for research on perceived legitimacy and justice, as well as their implications for understanding social class.